Dichloro‐Cycloazatriphosphane: The Missing Link between N2P2 and P4 Ring Systems in the Systematic Development of NP Chemistry. Issue 59 (9th October 2017) - Bresien, Jonas; Hinz, Alexander; Schulz, Axel; Suhrbier, Tim; Thomas, Max; Villinger, Alexander
Abstract: A dichloro‐cycloazatriphosphane that incorporates a cyclic NP3 backbone could be synthesized using knowledge gained from the chemistry of N2 P2 and P4 ring systems. It fills the gap between the congeneric compounds [ClP(μ‐NR)]2 and [ClP(μ‐PR)]2 (R=sterically demanding substituent), and thus contributes to the systematic development of nitrogen–phosphorus chemistry in general. The title compound was studied with respect to its formation via a labile aminodiphosphene, which readily underwent different rearrangement reactions depending on the solvent. All compounds were fully characterized by experimental and computational methods. Abstract : NP3 ring system : Starting from a highly reactive amino‐diphosphene, a dichloro‐cycloazatriphosphane (see Scheme) could be synthesized and fully characterized. This new ring system can be regarded as a congener of [XP(μ‐NR)]2 and [XP(μ‐PR)]2 systems and therefore contributes to a systematic development of NP chemistry.